PENGARUH LINGKUNGAN KERJA FISIK DAN NON FISIK TERHADAP KINERJA KARYAWAN (Studi Pada Karyawan Kantor PT. Perkebunan Nusantara X (Persero) Pabrik Gula Lestari Nganjuk) - Musyaya, Antonius Adek; Sudiro, Achmad (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2013)
The work environment is circumstances of the surrounding workplace in physical and non-physical manner that can give enjoyable, secure, reassuring, and feel work at home impressions. The working environment is very important because it is closely related to the level of the employee performance, if the working environment better, it could give a positive influence on employee’ performance, and vice versa. This study uses the